The impact of IDX-MES BUMN 17 shariah index launching on market reaction - Khotijah, Siti Afidatul; Fachrunnisa, Zidni Husnia; Khabibah, Nibras Anny (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2024)
Information circulating in the community will impact stock market reactions on the stock exchange. The reaction can be accounting or non-accounting. The launch of the IDX-MES BUMN 17 Index is one of the non-accounting information that can influence activity on the stock exchange, especially for entities included in the index. This study aims to identify stock market reactions included in the IDX-MES BUMN 17 index after the launch of the index. This research was conducted by testing stock prices and trading volume before and after the IDX-MES BUMN 17 index was published. This test is also supported by a comparative analysis of changes in stock prices and trading volume from the IDX-MES BUMN 17 index and the Indonesia Composite Index. This study's results indicate an increase in stock prices for 17 BUMN companies included in the IDX-MES BUMN 17 index after the launch of the index. In addition, this study found differences in stock trading volume before and after the index publication. This shows that the information is absorbed in the market, especially for investors concerned about Islamic stocks